Bar-Kokhba Revolt Coins (The Biblical archaeology review, 2024)
A Judean desert cave has yielded four rare coins from the time of the Bar-Kokhba Revolt (132-136 CE). Archaeologists from the Israel Antiquities Authority (IAA), in partnership with the Archaeological Office of the Military Administration of Judea and Samaria, discovered the coins during archaeological survey work at the cave, which is in the Mazuq ha-He’teqim […]